What would mathematicians do? Providing opportunities for reasoning and sense making. Issue 3 (26th May 2020) - Barlow, Elizabeth K.; Barlow, Angela T.
Abstract: Often, when middle-school students make mistakes, they tend to erase their work and record the correct answer without trying to understand what led to the mistake. In response, this article describes three opportunities educators can leverage for engaging students in the processes of reasoning and sense making about mathematics.